Tracking Animal-Dispersed Seedlings Using 15N Xylem Injection Method - Wang, Minghui; Yi, Sijie; Ju, Mengyao; Yi, Xianfeng (Frontiers in Plant Science, 2021)
Summary 1. Although various seed marking methods have been developed for seed dispersal, it still remains difficult to track the actual patterns of seed dispersal and seedling recruitment. Thus, new labeling methods that accurately track seedling establishment along with seed movement would help us better understand seed dispersal. 2. Here, we developed a new nondestructive method using 15N xylem injection to track seed dispersal and seedling recruitment based on the enriched isotopic signals in the mature seeds. 3. Our results first showed that xylem injection of 15N successfully enriched 15N both in the acorns and seedlings of Quercus variabilis. By marking acorns and seedlings with 15N stable isotopes, we successfully tracked seedlings established from acorns dispersed by seed-eating animals in the field. 4. Our xylem 15N injection caused little alteration to seeds and showed no significant effects on seed selection by seed-eating animals as well as seed germination and seedling establishment, verifying the validity of 15N xylem injection method to track seedling establishment. 5. Our xylem 15N injection method is expected to be a powerful tool for tracking seed dispersal and seedling recruitment mediated by seed-eating animals in seed dispersal ecology.